Sodium Alginate Modified Platinum Nanozymes With Highly Efficient and Robust Oxidase-Like Activity for Antioxidant Capacity and Analysis of Proanthocyanidins - He, Shao-Bin; Yang, Liu; Lin, Xiu-Ling; Peng, Hua-Ping; Lin, Zhen; Deng, Hao-Hua; Chen, Wei; Hong, Guo-Lin (Frontiers in Chemistry, 2020)
Platinum nanozymes exhibiting highly efficient and robust oxidase-like activity are successfully synthesized and modified using sodium alginate (SA-PtNPs). According to a steady-state dynamic assay, Michaelis-Menton constant (Km) is calculated as 11.6 μM, indicating that the affinity of SA-PtNPs towards the substrate, 3, 3', 5, 5'-tetramethylbenzidine (TMB), is high. It shows in the paper that SA-PtNPs exhibits a significant oxidant effect on substrate-O2 to produce O2•− as an oxidase mimic. Moreover, the oxidase-like activity fluctuated slightly under changes in environmental pH and incubation time, implying that SA can increase the dispersibility and stability of PtNPs. A colorimetric assay for oligomeric proanthocyanidins (OPC) was realized given how few explorations of the former there are. We found that the significant inhibitory effect of OPC on the oxidase-like activity is due to the competitive effect between OPC and TMB for binding to the active site of SA-PtNPs, resulting in a color change. Under optimal conditions, the logarithmic value of the chromogenic difference (ΔA450nm) to OPC concentration was linear (4–32.5 μM, r=0.999) with a limit of detection (LOD) of 2.0 μM. The antioxidant capacity of OPC obtained by the Soxhlet extraction method from grape seeds was 2.85 U/mg. The recovery from the experiment in which OPC was added to grape seeds ranged from 97.0–98.6 % (RSD of 0.5-3.4 %), suggesting a high accuracy in OPC detection. These findings are important because OPC is an internationally recognized antioxidant that eliminates free radicals in the human body and, therefore, may prevent a variety of diseases. Thus, we envisage that this Pt nanozyme-based assay may be prevalent for antioxidant capacity evaluation and analytical applications.